ҚАРАҚАЛПАҚСТАН АЙМАҒЫНДА ҚАЛАЛАРДЫҢ ГЕНЕЗИСИ ҲӘМ ТИПОЛОГИЯСЫ (Шымбай қаласы мысалында) - Есназарова, З.Б. (ILIM hám JÁMIYET, 2024)
The article examines the genesis and typology of cities in Karakalpakstan from a historical perspective. The development and location of the city of Chimbay, its specifics, and the demography of the twentieth century were mainly studied. The population are analyzed of cities in Karakalpakstan and the dynamics of population growth in the 18th and 20th centuries.